Covid-19 pandemic and university extension: Report of experiences in the educating for physical activity – EPA project with elderly people (Research, Society and Development, 2025)
The objective of this work is to describe the experiences regarding the remote activities of the “Educating for Physical Activity - EPA” project, as well as the strategies used to carry out the classes. Descriptive study, experience report type. A video tutorial, a folder to facilitate access to the meeting platform, and an assessment via online questionnaire were produced and sent to the elderly via WhatsApp before the activities began. Twenty-eight classes were taught remotely, consisting of a conversation circle, lectures, physical exercises (PE) taught by monitors, calming down and self-assessment. The participation frequency of elderly people was 44.5%. There was greater participation from the elderly person's family during classes. An improvement was observed in the functional autonomy of the elderly and in the handling of technology for recording videos with PE on alternative days to the meeting. It is concluded that the actions and strategies promoted by EPA enabled reflection on the topics covered, active participation of the elderly and their families, as well as the acquisition of skills for handling cell phones, thus facilitating access to the PE program guided and supervised by EPA teachers and monitors.